Design and Implementation of a Web Attack Analysis System Based on Honeypot Technology - Wang, Shuqian (International Journal of Computer Science and Information Technology, 2024)
Nowadays, with an increasing number of Web services being deployed in university network systems, Web attacks have become a significant threat due to the inherent vulnerabilities in Web services and the diverse forms of these attacks. Traditional Web attack defenses can only react passively, resulting in a lag in protection. Therefore, to enhance the security of Web systems, this paper develops a Web attack analysis system based on honeypot technology. Firstly, the system captures Web attack information through simulated honeypots. Secondly, it extracts and integrates effective data from the attack information to analyze hackers' attack methods and intentions. Thirdly, the analysis results are visualized through charts, providing data support for system maintenance. Finally, the feasibility of the system is verified through experiments.